Different functional responses in populations of Polylepis quadrijuga (Rosaceae) as a consequence of anthropogenic disturbance - Hoyos, Yessica D.; Vargas, Natalia; Sanchez, Adriana (Frontiers in Forests and Global Change, 2024)
The monodominant forests of Polylepis quadrijuga, endemic to the páramos of the eastern cordillera in the Colombian Andes, are among the most threatened in South America due to fragmentation and anthropogenic degradation. Despite their role in regulating water flow and forming biodiverse, endemic biotic communities, there are few studies on their functional responses to stress caused by anthropogenic disturbance and climate change. In this study, we evaluate how six different populations of P. quadrijuga with distinct levels of anthropogenic disturbance (low and high) change 11 foliar, stem, and root functional traits. Also, the physicochemical properties of the soils were analyzed, and mycorrhizal colonization was quantified to evaluate how each population responds to the stress conditions. The results indicated that populations with lower disturbance levels exhibit a conservative leaf trait configuration, whereas those with higher disturbance levels adopt an acquisitive strategy, potentially making them more vulnerable. Additionally, we found no functional coordination between above- and belowground traits. The results also highlight a lower percentage of arbuscular mycorrhizarl fungi (AMF) colonization in sites with a high level of disturbance. Our findings show P. quadrijuga’s sensitivity to anthropogenic disturbance and its resilience, demonstrated by high plasticity in aboveground traits. Conservation efforts for this endangered species should focus on fragmented populations and those under stress from grazing or agriculture, aiming to create connectivity and promote its establishment